Efficacy of Intrathecal Fentanyl for Cesarean Delivery: A Systematic Review and Meta-Analysis of Randomized Controlled Trials With Trial Sequential Analysis. Issue 3 (September 2019) - Uppal, V.; Retter, S.; Casey, M.; McKeen, D.M.
Abstract : ( Anesth Analg . 2019 Jan 8. doi: 10.1213/ANE.0000000000003975) Numerous studies have evaluated the risks and benefits of intrathecal fentanyl when added to bupivacaine during cesarean delivery. While potential advantages of intrathecal fentanyl over intrathecal morphine include faster onset and less cephalad spread, some have feared an increased risk of respiratory depression, a "ceiling effect" at doses >0.25 μg/kg, and increased postoperative intravenous opioid requirement. In order to clarify the benefits, harms, and optimal dosing of this opioid for cesarean delivery, these authors systematically reviewed evidence regarding the efficacy and safety of fentanyl when used as an additive to intrathecal bupivacaine with and without morphine.